Growing your library career with social media - Smith, Daniella (Chandos advances in information series., 2018)
Growing Your Career with Social Media presents social media tools, current trends and professional development strategies to help busy librarians remain up-to-date. This title offers advice from librarians on how to use social media for career development and continuing education. Advice is based on accumulated experience from professionals who have incorporated social media into their professional lives. The book includes interviews and suggests ways librarians can use social media as a tool for self-promotion. It includes tables of social media tools and their potential uses, and also provides resources, lists, organizations and information on librarians currently active in social media.